ChemInform Abstract: Synthesis and Antiplasmodial Evaluation of Novel (4‐Aminobutyloxy)quinolines. Issue 21 (2nd May 2013) - Vandekerckhove, Stephanie; Mueller, Christian; Vogt, Dieter; Lategan, Carmen; Smith, Peter J.; Chibale, Kelly; De Kimpe, Norbert; D'hooghe, Matthias
Abstract Title compounds [(VII), (IX), (XI), and (XIII)] are synthesized starting from corresponding hydroxyquinolines like (I) via a rhodium‐catalyzed hydroformylation as the key step.